Gender differences in carbohydrate loading are related to energy intake - Tarnopolsky, M. A.; Zawada, C.; Richmond, L. B.; Carter, S.; Shearer, J.; Graham, T.; Phillips, S. M. (Journal of Applied Physiology, 2001)
We demonstrated that female endurance athletes did not increase their muscle glycogen concentration after an increase in the dietary carbohydrate intake (58 74%), whereas men did (Tarnopolsky MA, SA Atkinson, SM Phillips, and JD McDougall, J Appl Physiol 78: 1360-1368, 1995). This may have been related to a lower energy or carbohydrate intake by the women or due to an inherent gender difference in glycogen storage capacity. We examined whether well-trained men (n = 6) and women (n = 6) increased muscle glycogen concentration after an increase in both the relative (58 75%) and absolute energy and carbohydrate intake and whether potential gender differences were related to muscle hexokinase enzyme activity. Subjects were randomly allocated to three diets [Hab, habitual; CHO, high carbohydrate (75%); and CHO + E, extra energy + CHO (~34%)] for a 4-day period before a muscle biopsy for analysis of total and pro- and macroglycogen and hexokinase activity. Total glycogen concentration was higher for the men on the CHO and CHO + E trials compared with Hab (P < 0.05), whereas women increased only on the CHO + E trial compared with Hab (P < 0.05). There were no gender differences in the proportion of pro- and macroglycogen or hexokinase activity. A low energy intake may explain the previously reported lower capacity for women to glycogen load compared with men.